BIOLOGY ACTIVITIES OF IgY PARVOVIRUS AFTER HEAT TREATMENT - Suartini, I Gusti Ayu Agung; Agustini, Ni Luh Putu; Setiasih, Ni Luh Eka; Putriningsih, Sisyawati; Nurwidana, Defi Lega (Buletin Veteriner Udayana, 2016)
This study aims to determine the effect of temperature on the biological activity of various crude and precipitate specific Immunoglobulin (Ig)Y Canine parvovirus (CPV). Hiperimun serum conducted on Isa Brown chickens injected with antigen CPV. Crude yolk Ig preparations derived from chicken serum without purification while the yolk Ig preparations precipitates obtained by the chicken serum was precipitated with ammonium sulfate and dialyzed. Both types of Ig yolk given treatment temperature 50ºC, 60ºC, 70ºC, and 80ºC for 15 minutes. To test Gel Precipitation Test (AGPT) is performed to determine whether there is a specific IgY CPV in the serum of chickens. Biological activity of both types of Ig detected with Barriers Haemagglutination test (HI). The design used in this study is completely randomized design factorial. The results of this study indicate that the temperature was highly significant on the activities of IgY crude and precipitates. Activities IgY crude and precipitate down to the treatment temperature of 50ºC, 60ºC, 70ºC, and 80ºC. Geometric Mean Titer crude IgY respectively - were 2 6.67 , 2 6 , 2 5.33 , and <2 º Unit HI while IgY precipitates are respectively 2 6.33 , 2 5.67 , 2 4 , and <2º Unit HI. Based on the results of this study concluded that the biological activity of crude IgY better than IgY precipitates after treatment of a wide range of temperatures.
Keywords: immunoglobulin yolk; crude; precipitates; canine parvovirus; temperature